Cutting temperatures in milling operations of difficult-to-cut materials - Soori, Mohsen; Asmael, Mohammed (Univ Larbi Ben Mhidi, 2021)
Due to high strength-to-weight ratio and corrosion resistance, difficult-to-cut materials are used in the aerospace, automotive and medical industries. High mechanical and thermal loading occur during machining operations of difficult-to-cut materials, reducing cutting tool life and machining process performance. So, analyzing the cutting temperatures in milling operations of difficult-to-cut materials can increase the efficiency in production process of the parts from the alloys. Application of the virtual machining system is developed in the study to predict the cutting temperature during machining operations of difficult-to-cut materials such as Inconel 718, Titanium alloy Ti6Al4V and Nickel-base superalloy gH4133B. The modified JohnsonCook model is used to analyze the coupled effects of strain rate and deformation temperature on flow stress during milling operations of the alloys. The finite element simulation of the milling operations is implemented for the alloys in order to obtain the cutting temperature of the cutting tool and workpiece during chip formation process. To validate the study, the experimental results are compared to the finite element results obtained from the virtual machining system. As a result, the study can provide an effective device in terms of efficiency enhancement of machining operations by analyzing and decreasing the cutting temperature in milling operation of difficult-to-cut materials.
Keywords: Cutting temperature; Difficult to Cut Materials; Modified JohnsonCook model; Virtual machining